2021
DOI: 10.3390/molecules26247555
|View full text |Cite
|
Sign up to set email alerts
|

Janerin Induces Cell Cycle Arrest at the G2/M Phase and Promotes Apoptosis Involving the MAPK Pathway in THP-1, Leukemic Cell Line

Abstract: Janerin is a cytotoxic sesquiterpene lactone that has been isolated and characterized from different species of the Centaurea genus. In this study, janerin was isolated form Centaurothamnus maximus, and its cytotoxic molecular mechanism was studied in THP-1 human leukemic cells. Janerin inhibited the proliferation of THP-1 cells in a dose-dependent manner. Janerin caused the cell cycle arrest at the G2/M phase by decreasing the CDK1/Cyclin-B complex. Subsequently, we found that janerin promoted THP-1 cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Our annexin V/PI staining experiment demonstrated that apoptosis is the primary mechanism involved in chlorojanerin-mediated cell death. In our previous study [ 21 ], the THP-1 leukemic cell line also showed similar apoptotic patterns following janerin treatment.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our annexin V/PI staining experiment demonstrated that apoptosis is the primary mechanism involved in chlorojanerin-mediated cell death. In our previous study [ 21 ], the THP-1 leukemic cell line also showed similar apoptotic patterns following janerin treatment.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, we show that chlorojanerin caused an accumulation of cells in the G2/M phase after 24 h of treatment. The scenario described here for the induction of G2/M phase cell cycle arrest in suppressing the proliferation of A549 cells has been demonstrated in our previous work with janerin compound that induced G2/M phase cell cycle arrest in human leukemia cancer cells [ 21 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The expression of Cyclin B and cdc2 was significantly decreased, but the expression of p-p53 and p21 upstream of them was remarkably increased ( Figure 3 C,D). The above results show that isorhamnetin can inhibit the proliferation of Ishikawa cells in the G2/M phase [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The expression of Cyclin B and cdc2 was significantly decreased, but the expression of p-p53 and p21 upstream of them was remarkably increased (Figure 3C,D). The above results show that isorhamnetin can inhibit the proliferation of Ishikawa cells in the G2/M phase [30]. In order to further investigate the mechanism of the cell cycle influenced by isorhamnetin, we investigated protein expression levels.…”
Section: Isorhamnetin Blocks the G2/m Phase In Ishikawa Cellsmentioning
confidence: 98%